Kepastian Hukum Badan Arbitrase dan Alternatif Penyelesaian Sengketa Konstruksi Indonesia dalam Perjanjian Penanaman Modal Asing di Sektor Konstruksi - Bayu Handoko; RR. Lyia Aina Prihadiati; Momon Mulyana (PT Elaborium Elevasi Indonesia, 2023)
The Indonesian government is committed to prioritizing the acceleration of development and infrastructure and construction as one of the drivers of the national economy. This makes Indonesia the largest construction market in ASEAN. In regard with these achievements, currently Indonesia is become the leading country for foreign construction companies to operate and develop their business. The standard legal research is used as a research method. The results of the study show that there are several cooperation agreements that can be entered into between foreign investors and domestic investors. In particular, the Construction Services Law on Cooperation Agreements for Foreign Investment in Construction Sector offers opportunities for foreign companies to engage in construction development projects through the establishment of joint ventures or joint operations with Indonesian companies. The legal certainty of the Indonesian Construction Arbitration and Alternative Dispute Settlement Agency as one of the bodies authorized to resolve disputes arising from cooperation agreements on foreign investment in the construction sector is based on Article 32 of Law Number 25 of 2007 concerning Investment, Article 88 Law Number 2 of 2017 concerning Construction Services, Law Number 30 of 1999 concerning Arbitration dan Alternative Dispute and Article 93 paragraph (1) Government Regulation Number 22 of 2020 concerning Implementation Regulations of Law Number 2 of 2017 concerning Construction Services, which states that the stages of efforts to resolve Construction disputes include Mediation, Conciliation and arbitration.